ETHNOGRAPHY OF COMMUNICATION: THE ANALYSIS OF DELL HYMES'S SPEAKING IN BALINESE WEDDING PROPOSAL - Diany Purnama Sari; Ni Putu Santhi Widiastuti; I Made Agus Adi Gunawan (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACT The present study conducted a qualitative descriptive method regarding ethnography of communication to analyze a Balinese wedding ceremony of a Balinese couple using Dell Hymes’s SPEAKING mnemonic. The research resulted that there was a relationship between speech event regarding Balinese wedding proposal and Dell Hymes’ SPEAKING mnemonic. The results showed that Balinese wedding proposal of a Balinese couple was held in Bale Dangin (setting) and people sat in a semicircular including father, mother, sibling, and also some close relatives such as grandparents, aunts, uncles, and so on (participants) to make an agreement to hold a wedding ceremony (ends). The sequenced of the proposal was started by proposee’s spokesman who delivered the opening then it was continued by the proposer’s spokesman (act of sequence). They were all in serious situation (key) by the use of code-mixing in delivering the speech (instrumentalities) to ensure about their commitment to live together (norms of interaction and interpretation). The genre was proposal which showed serious claim of reasoning of an action. Keywords: ethnography of communication; Dell Hymes’s SPEAKING; Balinese; wedding proposa